A Chinese Popularity Function: Sources of Government Support. (March 2014) - Lewis-Beck, Michael S.; Tang, Wenfang; Martini, Nicholas F.
The notion of a Chinese popularity function may seem surprising, given its authoritarian nature. However, exploring the possibility of indirect popularity functions in nondemocratic systems, we articulate a model of national government support in China. The model argues that sociodemographics, political attitudes, and performance issues mold central government satisfaction. Drawing on a countrywide 2008 public opinion survey, we conclude that regional differences, national trust, and local policy success are of special importance in shaping national government support. The findings, which exhibit theoretical and statistical appeal, lay the groundwork for further investigation of popularity functions in China.